Antibiotic resistance among clinical isolates of Haemophilus influenzae in the United States in 1994 and 1995 and detection of beta-lactamase-positive strains resistant to amoxicillin-clavulanate: results of a national multicenter surveillance study. - Doern, G; Brueggemann, A; Pierce, G; Holley, H; Rauch, A (1997)
A total of 1,537 clinical isolates of Haemophilus influenzae were recovered in 30 U.S. medical center laboratories between 1 November 1994 and 30 April 1995 and were characterized in a central laboratory with respect to serotype and beta-lactamase production and the in vitro activities of 15 oral antimicrobial agents. Overall, 36.4% of the isolates were found to produce beta-lactamase. The rank order of activity of six cephalosporins on the basis of MICs was cefixime > cefpodoxime > cefuroxime > loracarbef > or = cefaclor > cefprozil. On the basis of current National Committee for Clinical Laboratory Standards (NCCLS) breakpoints ages of isolates found to be resistant or intermediate to these agents were as follows: 0.1, 0.3, 6.4, 16.3, 18.3, and 29.8, respectively (National Committee for Clinical Laboratory Standards. Methods for dilution antimicrobial susceptibility tests for bacteria that grow aerobically, 4th ed. M7-A4, 1995). Azithromycin was, on a weight basis, the most potent of the macrolides tested in this study, followed by erythromycin and then clarithromycin. Azithromycin was typically fourfold more active than erythromycin, which was, in turn, slightly more active than clarithromycin. However, when compared on the basis of the frequency of resistance determined by using current NCCLS breakpoints, there was essentially no difference between azithromycin and clarithromycin, i.e., 0.5 and 1.9%, respectively (P = 0.086). Interpretive breakpoints for erythromycin MIC tests versus H. influenzae have not been developed. Resistance to other non- beta-lactam agents was variable, as follows: trimethoprim-sulfamethoxazole, 9.0%; chloramphenicol, 0.2%; tetracycline, 1.3%; and rifampin, 0.3%. Two conspicuous findings in this study were the identification of 39 strains H. influenzae that were beta-lactamase negative but ampicillin intermediate or resistant (BLNAR) and, even more surprisingly, 17 beta-lactamase-positive isolates that were resistant to amoxicillin-clavulanate (BLPACR). Strains of H. influenzae in the first group have heretofore been very uncommon; organisms in the second group have not previously been described in the literature. The percentages of all study isolates comprised of BLNAR and BLPACR organisms were 2.5 and 1.1, respectively. Overall resistance to ampicillin was thus 38.9%, and that to amoxicillin-clavulanate was 4.5%.